(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article shows that in the story "Bahouddinning iti " written by Nazar Eshanqul, the leader of modern Uzbek literature, the symbolic meaning of the dog is covered in different interpretations and explained in analytical ways. Also, through the image of a dog, the inner world of the hero who wants to overcome the satanic lust and realizing one’s own is highlighted.